Anisotropic mechanical behavior of two dimensional silicon carbide: effect of temperature and vacancy defects. (4th December 2019) - Islam, A S M Jannatul; Islam, Md Sherajul; Ferdous, Naim; Park, Jeongwon; Bhuiyan, Ashraful G; Hashimoto, Akihiro
Abstract: Mechanical stability, which is featured by high tensile strength, is one of the most critical concerns for the reliability of next-generation nanoelectromechanical systems (NEMS). Presently, sp 2 hybridized two-dimensional silicon carbide (2D-SiC) is supposed to be a novel nanomaterial to apply in nanocomposites, NEMS, and nano-energy harvesting applications because of its amazing electronic, mechanical and thermal properties. This paper explores the mechanical behavior, including fracture stress, fracture strain, and elastic modulus of both pristine and vacancy defected 2D-SiC at temperatures 300–700 K using molecular dynamics simulation. Two types of vacancy defects such as point and bi-vacancies with concentration 0.1%–1.0% are considered. Moreover, the effect of system size and strain rate on the mechanical behavior of 2D-SiC is also analyzed. A highly anisotropic mechanical behavior is found at all temperature and defect conditions. At 300 K, a fracture stress and an elastic modulus of 71.02 GPa and 637.26 GPa, respectively is obtained along the armchair direction, which is ∼24.42% and ∼14.38% higher compared to the zigzag directed fracture stress and elastic modulus. A reduction of fracture stress, fracture strain, and elastic modulus with the increase of temperature and defect concentration is also perceived in both armchair and zigzag directions. Moreover, due to the large symmetry breakdown by the point vacancy, a comparatively larger drastic reduction is noticed in the fracture behavior than the bi-vacancy at all temperatures and loading directions. These results would provide a new insight for solving the mechanical instability problem of SiC-based NEMS and nanodevices in the near future.